Paul M. Livingston and the Paradoxical Basis of Political Critique - Syutkin, Anton (Stasis, 2018)
Book review: Paul M. Livingston, The Politics of Logic: Badiou, Wittgenstein, and the Consequences of Formalism New York: Routledge, 2012, 394 pp., ISBN 9780415891912 Routledge Studies in Contemporary Philosophy (Book 27)